Integrating the Islamic perspectives in the fundamental safety principles to improve radiation protection culture among Muslim diagnostic radiographers - Ahmad Radzi, Halimatussa'Diah (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2018)
As one of the radiation personnel, diagnostic radiographers are responsible to ensure measures related to radiation protection are taken appropriately. However, the awareness towards radiation protection and safety were insufficient and there is a need to improve the radiation protection culture (RPC) among radiographers. Therefore, this paper aims to integrate the Islamic Perspectives in radiation fundamental safety principles which are related to diagnostic radiographer’s responsibility. Later, is to highlight the application of integrating the Islamic perspectives towards improving RPC among Muslim radiographers. Out of the 10 safety principles, radiographers are able to directly contribute in six principles which are the responsibility for safety, justification of facilities and activities, optimisation of protection, limitation of risk, protection of oneself and others as well as future generations, and prevention of accidents. The Islamic perspectives related to those principles were taken from Al-Quran, hadith and Maqasid al-Shariah. They are related to the concept of responsibility, beneficence, justice, moderation (al-wasatiyyah), do no harm, protection of life and prevention from harm from the Islamic perspectives. In order to improve RPC, education and training of the involved professionals as well as adequate communication are important. Incorporating Islamic perspectives of radiation safety principles during the training session and constantly reminding the Muslim radiographers of those Islamic perspectives through poster display can be done. It is hopeful that by realizing the principles of radiation safety are in line with the teaching of Islam, Muslim radiographers will be more involved in the RPC programmes in the department.